Analisis Pengaruh Good Corporate Governance dan Konservatisme Akuntansi Terhadap Tax Avoidance - Herman Sjahruddin; Karyaningsih Karyaningsih; Rini Novianti; Rian Ardianto; Sonny Santosa (ITB AAS INDONESIA, 2023)
This study aims to examine and analyze the effect of good corporate governance and accounting conservatism on tax avoidance. This type of research is an explanation research with a quantitative approach. The independent variables in this study are good corporate governance and conservatism. While the dependent variable in this study is tax avoidance. The data used in this research is quantitative by analyzing secondary data. The population listed in this study consists of property companies during the 2016-2021 period. Where this research was conducted by means of a survey to the Indonesia Stock Exchange. The collected data is processed and analyzed by multiple linear regression analysis with the help of SPSS 23 program. The results of this study indicate that: 1) good corporate governance has a positive and significant effect on tax avoidance and 2) conservatism has a positive and significant effect on tax avoidance. The results of this study suggest that if the company wants to do tax avoidance well, the company must understand good corporate governance and accounting conservatism so that tax avoidance by the company does not have a negative impact on the company in the long term.